The use of 2x4 orthodontic appliance for interseptive treatment - Eka Erwansyah; Nurmala Dewi; Eddy Heriyanto Habar (Makassar Dental Journal, 2020)
Background : The mixed tooth phase is the most important phase in the growth and development of the child's teeth and jaw. Interseptive treatment is given to children who experience a mixed dental phase, starting at the age of 7-8 years because at the age of 8 year permanent molars and permanent incisors have erupted. Early malocclusion’s treatment can avoid the occurrence of malocclusion and building the confidence in patients. The 2x4 appliance is a tool that provides good stability, which is applied to the first molars and erupted incisors. Conclusion : The corrections of malocclusion do not have to wait until the eruption of all permanent teeth. Waiting for eruption all permanent teeth will aggravate malocclusion and will make the treatment harder, such as treatments that require orthodontic surgical treatment, and extraction of permanent teeth. Treatment of malocclusion at an early age (7-8 years) will ease the correction of malocclusion because it is the age of growth and development of the jaw so the treatment time will be shorter compared to conventional orthodontic treatment.